Intracerebroventricular knockdown of NPY1R disrupts NPY1R-GALR2/TrkB heteroreceptor complexes without affecting neuroplasticity or depressive-like behaviour - Moreno-Madrid, Isabel; Arrabal-Gómez, Carlos; Romero-Imbroda, Jesús; Díaz-Casares, Amelia; Fuxe, Kjell; Borroto Escuela, Dasiel Óscar; Serrano-Castro, Pedro Jesús; Narváez-Peláez, Manuel (Sage, 2025)
Background:Neuropeptide Y1 receptor (NPY1R) heteroreceptor complexes with galanin receptor 2 (GALR2) and Tropomyosin receptor kinase B (TrkB) contribute to neuroplasticity and mood regulation. Aims:To determine whether transient intracerebroventricular (ICV) knockdown of NPY1R is sufficient to alter hippocampal neurogenesis and depressive-like behaviour. Methods:Adult Sprague-Dawley rats received a single ICV injection of Accell Smart-Pool small interfering RNA (siRNA) targeting NPY1R or a scrambled control. NPY1R protein levels, NPY1R-GALR2 and NPY1R-TrkB complexes (in situ proximity ligation), proliferating cell nuclear antigen (PCNA) counts, brain-derived neurotrophic factor (BDNF) expression and forced-swim behaviour were assessed 6, 8 and 10 days post-injection in the ventral hippocampus. Results:ICV siRNA significantly reduced NPY1R immunoreactivity (peak at day 8; p<0.05) and lowered NPY1R-GALR2 and NPY1R-TrkB heteroreceptor complexes (p<0.01 and p<0.001, respectively). PCNA-positive cell numbers and BDNF optical density were unchanged at all time points. Forced-swim immobility, climbing and swimming times likewise remained unaltered. Conclusions:Transient ICV knockdown effectively disrupts NPY1R heteroreceptor complexes but fails to impact neurogenesis or depressive-like behaviour, indicating compensatory mechanisms that preserve hippocampal plasticity. Within the time window and conditions tested, transient NPY1R knockdown disrupted GALR2/TrkB heteroreceptor complexes without altering neurogenesis or depressive-like behaviour, delineating receptor-complex-level target engagement and motivating studies using sustained and circuit-specific manipulations to assess therapeutic potential.
Keywords: Neurorreceptores; Receptores celulares; Neuroplasticidad; Hipocampo (Cerebro); Depresión mental; Neuropeptide Y1 receptor (NPY1R); Heteroreceptor complexes (GALR2/TrkB); Intracerebroventricular siRNA knockdown; Hippocampal neuroplasticity; Depressive-like behaviour